UJI TOKSISITAS SUBKRONIS EKSTRAK ETANOL DAUN SALAM TERHADAP HISTOPATOLOGI PARU MENCIT BETINA GALUR DDY - Rhea Veda Nugraha; Endah Hamidah Abbas; Titania Malafaizafatah; Yuke Ireka (Fakultas Kedokteran Universitas Jenderal Achmad Yani, 2026)
Bay leaf (Syzygium polyanthum) is widely used in Indonesia as a traditional medicine. Despite its many pharmacological benefits, prolonged use at high doses can lead to toxic effects. Therefore, its safety should be evaluated through toxicity testing. This study aimed to evaluate lung histopathological changes in female DDY mice following subchronic administration of ethanolic bay leaf extract. This experimental study employed a post-test only control group design. Twenty-eight female DDY mice were divided into four groups and treated for 28 days. One control group and three treatment groups receiving ethanolic bay leaf extract (EEDS) orally at doses of 250, 500, and 1000 mg/kg BW. Using Hematoxylin–Eosin (HE) staining, lung histopathology was examined semi-quantitatively based on the degree of inflammatory cell infiltration and alveolar septal damage under 400× magnification. The results of the study showed that subchronic administration of ethanolic bay leaf extract at all treatment doses did not produce significant differences in lung histopathology compared with the control group. The lung histopathological appearance across all groups was similar, with mild changes that remained within normal limits and did not indicate significant toxic effects. These findings may be attributed to the bioactive compounds present in bay leaves, including flavonoids, tannins, saponins, polyphenols, essential oils, and vitamin C, which exhibit antioxidant and anti-inflammatory activities. In conclusion, the administration of ethanolic bay leaf extract at doses of up to 1000 mg/kg BW during the subchronic period appears to be relatively safe for the lungs of female DDY mice. Keywords: bay leaves, female mice, histopathology, lung, subchronic toxicity DOI 10.35990/mk.v9n2.p210-220